Preventing Coronary Occlusion in an Elderly Severe Aortic Stenosis Patient with Critically Low Coronary Heights – A Case Report - Kumar, Viveka (Journal of Cardiology and Cardiovascular Medicine, 2023)
Background: Transcatheter Aortic Valve Replacement (TAVR) is an established treatment for severe, symptomatic Aortic Stenosis (AS). However, the presence of low coronary heights confers a high risk for coronary obstruction during or after TAVR. Case: In this case report, we present our experience with transfemoral-TAVR in an elderly, high-risk (STS score – 12.08%) female severe AS patient with low coronary heights (right: 7.4 mm, left: 8.7 mm). She had lower annulus area (287 mm2) and moderately low valve area (0.7 cm2) as well. Her mean and peak pressure gradients (PGs) were 38 mmHg and 61 mmHg, respectively. Upon the Heart Team’s evaluation, TAVR was recommended and a 20 mm Balloon Expandable (BE) Myval Transcatheter Heart Valve (THV) was selected. No peri-procedural or post-procedural complications were reported and the post-procedural hemodynamics, namely the mean and peak PGs improved to 16 mmHg and 30 mmHg after TAVR, respectively. The patient was discharged in a stable condition after four days of hospital stay. Conclusion: We report the successful implantation of a small-sized BE Myval THV (20 mm) in a patient with low coronary heights. Life-threatening complications including paravalvular leak, coronary obstruction, or annular rupture were well averted; hence, we ascertain that the Myval THV is a suitable device for treating severe AS in difficult anatomies. However, the viability of the novel valve needs to be reaffirmed in larger studies